ANALISIS PENGARUH BEBAN EKSTERNAL TERHADAP DISTRIBUSI REGANGAN PADA PIPA MELALUI PENDEKATAN FINITE ELEMENT METHOD - Risnawati, Faradilla Fauziyah; Huda, Muhammad Arif Nur; Kautzar, Galuh Zuhria; Septiawan, Diama Rizky (Steam Engineering, 2025)
This study aims to analyse the effect of external loading on the distribution of plastic strain in API 5L X80 steel pipes using the Finite Element Method. External loading was modelled through an indentation process using a spherical indenter with diameter variations of 75 mm, 100 mm, and 125 mm, and indentation depths of 2 mm, 3 mm, and 4 mm. The simulation was conducted under zero internal pressure conditions to evaluate the plastic strain distribution formed after loading. The results show that increasing the indentation depth significantly increases the maximum plastic strain value and expands the deformation area on the pipe wall. Conversely, increasing the indenter diameter tends to reduce the maximum plastic strain value but broadens the affected area of strain distribution. The maximum strain concentration is located at the dent’s flank rather than the root, which is caused by the load distribution from the spherical indenter toward the transition area. These findings highlight the importance of dent geometry parameters in predicting the plastic strain response of pipes, providing valuable insights for assessing the structural integrity of pipelines in oil and gas industry applications